STUDY KASUS DAMPAK DAN PENANGANAN KEKERASAN SEKSUAL TERHADAP REMAJA DAN ANAK - Rifki Amar Muafak; Edy Soesanto, Fachri Dwi Abdillah (CV. Adiba Aisha Amira, 2024)
Cases of sexual violence against children are still a phenomenon. This is because most children who are victims of sexual violence are reluctant to report it. Therefore, as parents you must be able to recognize the signs that your child is experiencing sexual violence. Sexual violence against children will have a long- lasting impact, apart from having an impact on health problems later in life, it is also associated with prolonged trauma, even into adulthood. The impact of trauma resulting from sexual violence experienced by children includes: betrayal or loss of children's trust in adults (betrayal); sexual trauma (traumatic sexualization); feeling helpless (powerlessness); and stigma (stigmatization). Psychologically, it can cause addiction, trauma, and even revenge. If it is not treated seriously, handling and healing psychological trauma resulting from sexual violence must receive great attention from all parties involved, such as family, society and the state. Therefore, in providing protection for children there is a need for a systems approach, which includes a social welfare system for children and families, a justice system that is in accordance with international standards, and mechanisms to encourage appropriate behavior in society.